Pengaruh Kompetensi Penyidik dan Kepercayaan Pada Kepemimpinan Terhadap Kinerja Anggota Satuan Reskrim - Iswahyudi, Agung; Setiono, Joko; Prianggono, Jarot (Prisani Cendekia, 2025)
The research findings indicate that investigator competence has a significant influence on the performance of the Criminal Investigation Unit members of Tanah Laut Police Precinct. The multiple linear regression test results show that investigator competence (X1) has a regression coefficient of 1.525 with a significance value of 0.000 (< 0.05). The partial t-test results also confirm that investigator competence significantly affects the performance of unit members. Similarly, trust in leadership also has a significant influence on the performance of the Criminal Investigation Unit members of Tanah Laut Police Precinct. The multiple linear regression test results indicate that trust in leadership (X2) has a regression coefficient of 0.551 with a significance value of 0.000 (< 0.05). The partial t-test results further confirm that trust in leadership significantly affects the performance of unit members. Investigator competence and trust in leadership jointly have a significant influence on investigator performance. The multiple linear regression test results show that investigator competence (X1) has a regression coefficient of 1.525, and trust in leadership (X2) has a regression coefficient of 0.551, with a significance value of 0.000 (< 0.05), indicating that both variables simultaneously enhance investigator performance.The coefficient of determination (Adjusted R Square) test result of 0.856 indicates that 85.6% of the variation in investigator performance can be explained by investigator competence and trust in leadership, while the remaining 14.4% is influenced by other factors. The R-value of 0.927 demonstrates that the relationship between the two independent variables and investigator performance is very strong.